An NMR‐Based Biosensor to Measure Stereospecific Methionine Sulfoxide Reductase Activities in Vitro and in Vivo. Issue 65 (14th October 2020) - Sánchez‐López, Carolina; Labadie, Natalia; Lombardo, Verónica A.; Biglione, Franco A.; Manta, Bruno; Jacob, Reeba Susan; Gladyshev, Vadim N.; Abdelilah‐Seyfried, Salim; Selenko, Philipp; Binolfi, Andres
Abstract: Oxidation of protein methionines to methionine‐sulfoxides (MetOx) is associated with several age‐related diseases. In healthy cells, MetOx is reduced to methionine by two families of conserved methionine sulfoxide reductase enzymes, MSRA and MSRB that specifically target the S ‐ or R ‐diastereoisomers of methionine‐sulfoxides, respectively. To directly interrogate MSRA and MSRB functions in cellular settings, we developed an NMR‐based biosensor that we call CarMetOx to simultaneously measure both enzyme activities in single reaction setups. We demonstrate the suitability of our strategy to delineate MSR functions in complex biological environments, including cell lysates and live zebrafish embryos. Thereby, we establish differences in substrate specificities between prokaryotic and eukaryotic MSRs and introduce CarMetOx as a highly sensitive tool for studying therapeutic targets of oxidative stress‐related human diseases and redox regulated signaling pathways. Abstract : Simultaneous activity measurements of MSRA and MSRB enzymes by NMR. CarMetOx is a synthetic biosensor to monitor the reduction of oxidized methionine residues by methionine sulfoxide reductase (MSR) enzymes. Based on NMR detection of R ‐ and S ‐ diastereoisomers of the isotope‐labelled reporter, stereospecific activities of class A ( R ‐) and class B ( S ‐) MSRs can be measured simultaneously in vitro and in vivo.